Pengaruh Likuiditas, Leverage, dan Profitabilitas terhadap Harga Saham (Studi Kasus pada Bank Panin Dubai Syariah) - Renazha Putri Audita; Hasbi Assidiki Mauluddi; Ade Ali Nurdin; Endang Hatma Juniwati (Journal of Applied Islamic Economics and Finance, 2023)
This study aims to determine how the influence of liquidity, leverage, and profitability on stock prices at Bank Panin Dubai Syariah Tbk period 2014-2020. This research uses causal associative method and is included in quantitative research. The ratios used in this research are Curret Ratio, Debt To Equity Ratio, and Return On Assets. The data used is secondary data, namely financial statement data and annual stock price reports that have been published on the official pages of each bank. This study uses the classical assumption test, multiple linear regression test, and the coefficient of determination test and uses the F test and t test to test the hypothesis with the IBM SPSS version 26 tool. The results of this show that: a). Current ratio, Debt to Equity, and Return on Assets simultaneously have no significant effect on stock prices, b). High Current Ratio (CR) will affect investor interest in investing in the company, c). Debt on Equity has a significant effect on stock prices, d) Stock Return is influenced by the Current Ratio (CR), Return On Assets (ROA), and Debt to Equity Ratio (DER) of 85.7% while the remaining 14.3% is influenced by other variables not examined in this study.